Thermal performance analysis of automotive radiator utilizing nanofluid coolants containing Fe nanoparticles - Taskesen, Edip; Gurbuz, Huseyin (Wiley, 2025)
In this study, the effect of Fe/water nanofluid on thermal performance under forced convection conditions in automotive radiators was experimentally investigated. A specially designed experimental setup was established, and tests were conducted at different flow rates and three different nanoparticle concentrations (0.015%, 0.030%, and 0.045% by weight (wt)). In certain cases, both the heat transfer rate and the temperature difference between the inlet and outlet decreased during system operation, indicating dynamic thermal behavior influenced by nanoparticle concentration and flow conditions. The findings revealed that the use of Fe/water nanofluid increased the radiator's total heat transfer capacity compared to water, and the nanoparticles had a positive effect on thermal conductivity. Experimental results showed that at flow rates of 8 LPM (Liters per minute), the nanofluid improved heat transfer performance by 1.86%, 3.49%, and 3.34% for Fe concentrations of 0.015, 0.030 , and 0.045 wt.%, respectively. However, it was observed that the performance increase was limited beyond a certain level as the concentration increased. This suggests the existence of an optimum concentration range for nanofluids. Additionally, some experimental results throughout the study period showed decreases in both the heat transfer rate and the inlet-outlet temperature difference with time. Overall, the findings suggest that the Fe/water nanofluid has the potential to increase the energy efficiency of automotive radiators.
Keywords: heat transfer; nanofluid and nanocoolant; nanoparticle; vehicle radiator